Confirmed adult dengue deaths in Singapore: 5-year multi-center retrospective study - Narayanan Rajmohan L; Oh Helen M; Low Jenny G; Fisher Dale A; Thein Tun L; Leo Yee-Sin; Gan Victor C; Lee Vernon J; Lye David C (BMC Infectious Diseases, 2011)
Abstract Background Dengue re-emerges in Singapore despite decades of effective vector control; the infection predominantly afflicts adults. Severe dengue not fulfilling dengue hemorrhagic fever (DHF) criteria according to World Health Organization (WHO) 1997 guideline was increasingly reported. A new WHO 2009 guideline emphasized warning signs and a wider range of severe dengue manifestations. We aim to evaluate the utility of these two guidelines in confirmed adult dengue fatalities. Methods We conducted a multi-center retrospective chart review of all confirmed adult dengue deaths in Singapore from 1 January 2004 to 31 December 2008. Results Of 28 adult dengue deaths, median age was 59 years. Male gender comprised 67.9% and co-morbidities existed in 75%. From illness onset, patients presented for admission at a median of 4 days and death occurred at a median of 12 days. Intensive care admission was required in 71.4%. Probable dengue was diagnosed in 32.1% by WHO 1997 criteria and 78.6% by WHO 2009. The earliest warning sign was persistent vomiting at a median of 1.5 days. Hematocrit change ≥20% concurrent with platelet count <20 × 10^9/L was associated with the shortest interval to death at a median of 3 days. Only 35.7% of death cases fulfilled DHF criteria by WHO 1997 versus severe dengue in 100.0% by WHO 2009 criteria. Deaths were due to shock and organ failure. Acute renal impairment occurred in 71.4%, impaired consciousness 57.1% and severe hepatitis 53.6%. Conclusions In our adult fatal dengue cohort, WHO 2009 criteria had higher sensitivity in diagnosing probable dengue and severe dengue compared with WHO 1997. As warning signs, persistent vomiting occurred early and hematocrit change ≥20% concurrent with platelet count <20 × 10^9/L preceded death most closely.